2004
DOI: 10.1080/07315724.2004.10719422
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-Content ofRhizobiumNodules in Different Plants: The Importance of Magnesium in Nitrogen-Fixation of Nodules

Abstract: Our results clearly show that the Mg nutrition treatment increased the number of Rhizobium nodules and their Mg-content, resulting in increased N2-fixation and yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 2 publications
5
10
1
Order By: Relevance
“…As expected, Mg-treated soybean plants had more and larger nodules. Similar results were reported by Kiss et al, 27 and they considered that Mg has an important role in the metabolism of the rhizobium bacteria and nodule development because (N 2 )fixing rhizobium strains need ATP that must be present as a Mg complex. 27 Another possible contributing mechanism for the positive influence of Mg addition on rhizobium bacteria may be the increase of carbon flow to root induced by Mg addition, 1 making more nutritional C available to rhizobium for growth.…”
Section: Journal Of Agricultural and Food Chemistrysupporting
confidence: 88%
“…As expected, Mg-treated soybean plants had more and larger nodules. Similar results were reported by Kiss et al, 27 and they considered that Mg has an important role in the metabolism of the rhizobium bacteria and nodule development because (N 2 )fixing rhizobium strains need ATP that must be present as a Mg complex. 27 Another possible contributing mechanism for the positive influence of Mg addition on rhizobium bacteria may be the increase of carbon flow to root induced by Mg addition, 1 making more nutritional C available to rhizobium for growth.…”
Section: Journal Of Agricultural and Food Chemistrysupporting
confidence: 88%
“…In previous studies, Vincent et al ( 1962 ) reported the failure of rhizobial cell division in Mg-deficient growth media. Conversely, Kiss et al ( 2004 ) observed a higher number of and larger nodules in pea roots treated with Mg in comparison to untreated roots. These findings indicate the importance of Mg in nodule formation and rhizobium activity in the roots, such as proliferation and nitrogen fixation.…”
Section: Discussionmentioning
confidence: 93%
“…Redundancy analysis and variance partitioning analysis identi ed that soil exchangeable Magnesium (Mg 2+ ) and daidzein were signi cantly associated with a rhizosphere microbial shift. Mg 2+ plays an important role in the metabolism of rhizobia and the development of nodules, because nitrogen-xing requires ATP present as a Mg 2+ -complex [97]. Thus, wild-type rhizobial strains require more magnesium from the soil than symbiosis defective ones.…”
Section: Discussionmentioning
confidence: 99%